Multiphase catalytic reactors : theory, design, manufacturing, and applications - Önsan, Zeynep Ilsen; Avci, Ahmet Kerim (John Wiley & Sons Inc., 2016)
-Provides a holistic approach to multiphase catalytic reactors from their modeling and design to their applications in industrial manufacturing of chemicals -Covers theoretical aspects and examples of fixed-bed, fluidized-bed, trickle-bed, slurry, monolith and microchannel reactors -Includes chapters covering experimental techniques and practical guidelines for lab-scale testing of multiphase reactors -Includes mathematical content focused on design equations and empirical relationships characterizing different multiphase reactor types together with an assortment of computational tools -Involves detailed coverage of multiphase reactor applications such as Fischer-Tropsch synthesis, fuel processing for fuel cells, hydrotreating of oil fractions and biofuels processing.